2017
DOI: 10.3802/jgo.2017.28.e82
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and oncologic outcomes after robotic radical hysterectomy as compared to open radical hysterectomy in the treatment of early cervical cancer

Abstract: ObjectiveThe use of robotic radical hysterectomy has greatly increased in the treatment of early stage cervical cancer. We sought to compare surgical and oncologic outcomes of women undergoing robotic radical hysterectomy compared to open radical hysterectomy.MethodsThe clinic-pathologic, treatment, and recurrence data were abstracted through an Institutional Review Board-approved protocol at 2 separate large tertiary care centers in Seattle, Swedish Medical Center and the University of Washington. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 36 publications
7
77
1
1
Order By: Relevance
“…Previous retrospective studies have indicated that there is no survival difference between robot-assisted and abdominal approaches, which is consistent with our results [17][18][19][20][21]. In addition, even when stratified by tumor size, oncologic outcomes were not significantly different between laparoscopic and abdominal approaches, which may emphasize the importance of the learning curve over the mode of surgery itself [22,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous retrospective studies have indicated that there is no survival difference between robot-assisted and abdominal approaches, which is consistent with our results [17][18][19][20][21]. In addition, even when stratified by tumor size, oncologic outcomes were not significantly different between laparoscopic and abdominal approaches, which may emphasize the importance of the learning curve over the mode of surgery itself [22,23].…”
Section: Discussionsupporting
confidence: 91%
“…However, many gynecologic oncologists suspect that this could not sufficiently support evidence that properly trained surgeons contributed in the MIS arm [27]. Also, we should focus on the result that only 7 recurrences (2.2%) were observed in the 312 women in the open surgery arm, which is an extremely low rate of recurrence comparing with previous reports, whereas 27 (8.4%) recurrences were noted in the MIS arm, which is comparative to the data reported in previous studies [18,19,23,28,29]. This observation suggested that the surgeons who already had overcome the learning curve for MIS; therefore, adopting the MIS approach for cervical cancer as the first option might have been excluded in the LACC trial at the beginning.…”
Section: Discussionmentioning
confidence: 56%
“…The data on oncological safety consisted until last year of retrospective observational cohorts of 100-500 patients with a follow up time from 30-60 months. These studies are consistent in regards to recurrence rate of 9-13% for patients operated on with robotically assisted radical hysterectomy (RRH) with no statistically significant difference when compared to abdominal radical hysterectomy (ARH) cohorts (48)(49)(50)(51). The results from the LACC trial, a phase III, multi-center non-inferiority Randomized controlled trial to comparing the outcomes of Laparoscopic Radical Hysterectomy (either conventional or robotically assisted) to ARH was published last year.…”
Section: Radical Surgerymentioning
confidence: 79%
“…Between 2008 and 2015, 3563 radical hysterectomies were performed based on the National Inpatient Sample (NIS) data, of which 27.5% were performed using a minimally invasive approach (robotic and laparoscopic) . Prior studies have demonstrated that compared to an open approach, minimally invasive (laparoscopic or robotic) techniques are associated with decreased blood loss, fewer complications, and a shorter hospital stay . Additional retrospective studies demonstrated no differences between robotic‐assisted radical hysterectomy and open surgery in regards to recurrence rates or death (Table ) …”
Section: Current Indicationsmentioning
confidence: 99%